2015
DOI: 10.1103/physreva.92.063407
|View full text |Cite
|
Sign up to set email alerts
|

Dynamical phases in a one-dimensional chain of heterospecies Rydberg atoms with next-nearest-neighbor interactions

Abstract: We theoretically investigate the dynamical phase diagram of a one-dimensional chain of laserexcited two-species Rydberg atoms. The existence of a variety of unique dynamical phases in the experimentally-achievable parameter region is predicted under the mean-field approximation, and the change of those phases when the effect of the next-nearest neighbor interaction is included is further discussed. In particular we find the competition of the strong Rydberg-Rydberg interactions and the optical excitation imbal… Show more

Help me understand this report
View preprint versions

Search citation statements

Order By: Relevance

Paper Sections

Select...
4
1

Citation Types

0
12
0

Year Published

2016
2016
2020
2020

Publication Types

Select...
6

Relationship

0
6

Authors

Journals

citations
Cited by 15 publications
(12 citation statements)
references
References 40 publications
0
12
0
Order By: Relevance
“…The reason for this is that they allow the state measurements to possess cross entanglement of two different atomic species located in the same trap, or nearby traps. The feasibility of this scheme was discussed in [16][17][18], and experimental research relevant to heteronuclear atom qubits was reported in Rb isotopes [19]. Since the heteronuclear atom qubits need the prepreparation of ultracold alkali metal dimers, only several combinations of them enable keeping stable under two-body molecular collisions [20].…”
Section: Introductionmentioning
confidence: 99%
“…The reason for this is that they allow the state measurements to possess cross entanglement of two different atomic species located in the same trap, or nearby traps. The feasibility of this scheme was discussed in [16][17][18], and experimental research relevant to heteronuclear atom qubits was reported in Rb isotopes [19]. Since the heteronuclear atom qubits need the prepreparation of ultracold alkali metal dimers, only several combinations of them enable keeping stable under two-body molecular collisions [20].…”
Section: Introductionmentioning
confidence: 99%
“…Interestingly, a system of coupled resonators in the photon-blockade regime arranged according a lattice geometry can be mapped into an effective spin model [21,26,27]. This class of systems can be realized nowadays using different experimental platforms, such as superconducting quantum simulators [28] or Rydberg atoms [29][30][31][32].…”
Section: Introductionmentioning
confidence: 99%
“…where we have inserted the density matrix expansion given in Eq. (5). If we allow t → ∞ so we study the two-time correlator in the steady state, then Eq.…”
Section: Quantum Phase Diagrammentioning
confidence: 99%
“…Although not as well understood as their equilibrium counterparts, non-equilibrium phenomena are in fact rather prevalent, as any experiment has some form of interaction with an environment, which will induce dissipative processes. Whereas these processes could be viewed as a nuisance, recent studies have shown that the interplay between an external drive and dissipation can produce exotic non-equilibrium phases such as spin density waves (SDW), antiferromagnetic phases (AFM), persistent long-time oscillations (OSC) and phase bistabilities within spin−1/2 systems [1][2][3][4][5][6] and higher spin systems [7]. Therefore, understanding the long-time steady state phases that can occur in open quantum systems is an intense area of current research.…”
Section: Introductionmentioning
confidence: 99%